Alkyl–aryl ketone synthesis via nickel-catalyzed reductive coupling of alkyl halides with aryl acids and anhydrides1. Issue 51 (28th June 2015) - Jia, Xiao; Zhang, Xinghua; Qian, Qun; Gong, Hegui
<x xml:space="preserve">Abstract</x> The efficient construction of alkyl–aryl ketones can be readily achieved from the reductive coupling of unactivated alkyl and 1-glycosyl bromides with 1.5 equiv. of aryl acids and their anhydrides.